1984
DOI: 10.1093/nar/12.24.9349
|View full text |Cite
|
Sign up to set email alerts
|

Human Cu/Zn superoxide dismutase gene: molecular characterization of its two mRNA species

Abstract: Two cytoplasmic superoxide dismutase (SOD-1) mRNAs of about 0.7 and 0.9 kilobases (Kb.) were previously found in a variety of human cells. The two SOD-1 mRNAs are transcribed from the same gene and the major 0.7 Kb. species is approximately four times more abundant than the minor 0.9 Kb. mRNA. These two mRNAs differ in the length of their 3'-untranslated region and both have multiple 5'-ends. The longer transcript contains 222 additional nucleotides beyond the 3'-polyadenylated terminus of the short mRNA. S1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…The first is that a locus for familial AD has been identified on chromosome 21 (26). The second is that the gene for the putative precursor of the amyloid ( protein, which is deposited in the neurons and cerebral vessels of individuals with AD, is also on chromosome 21 (27)(28)(29)(30), in the same vicinity as the familial AD locus (26,27 In addition to their relevance to the study of DS and AD, the h-CuZnSOD transgenics will also be of importance in the investigation of the role of CuZnSOD in protection against the adverse effects of a variety of exogenous agents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is that a locus for familial AD has been identified on chromosome 21 (26). The second is that the gene for the putative precursor of the amyloid ( protein, which is deposited in the neurons and cerebral vessels of individuals with AD, is also on chromosome 21 (27)(28)(29)(30), in the same vicinity as the familial AD locus (26,27 In addition to their relevance to the study of DS and AD, the h-CuZnSOD transgenics will also be of importance in the investigation of the role of CuZnSOD in protection against the adverse effects of a variety of exogenous agents.…”
Section: Resultsmentioning
confidence: 99%
“…USA 84 (1987) dodecyl sulfate/200 Ag of proteinase K per ml and incubated at 50'C for 12-16 hr. DNA was extracted and analyzed as described (21). DNA (10 ,ug) was digested with either Bgl II or Pst I and blot-hybridized with either a 32P-labeled 1.3-kb HindIII fragment of the h-CuZnSOD gene ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 0.45-kilobase (kb) 32 P-labelled antisense Cu,Zn-SOD cRNA was synthesized using a Xho I linearized SP65 vector containing the 450-bp Alu I to Taq I human Cu,Zn-SOD cDNA insert [15], as previously described [16]. A 0.468-kb 32 P-labelled antisense catalase cRNA was synthesized using a Xho I linearized SP65 vector containing the 1250-bp Hind III to Pvu II human catalase cDNA insert [17], as previously described [16].…”
Section: Methodsmentioning
confidence: 99%
“…However, two size classes of SOD-1 mRNAs, which differ by 200 nucleotides in their 3Ј UTRs, have been detected in certain human somatic tissues (61,62). Recently, it has been shown that the longer somatic SOD-1 mRNA produces three times more enzyme when transfected into COS 1 and human 293 cells than the shorter SOD-1 mRNA (36).…”
mentioning
confidence: 99%